(untitled) (Bangladesh Journal of Agricultural Research, 2007)
A study was undertaken to find out the effect of seven pH levels, six temperature regimes, five light durations and five incubation periods on radial colony growth and spore production of Stemphylium botryosum in petridishes (90 mm diameter) containing carrot dextrose agar (CDA) medium. Higher colony growth and spore production were reccorded within the pH range of 6-8, temperature regime of 20-25°C and incubation period of 5-25 days as compared to other levels of each growth factors. The maximum mycelial growth and sporulation was observed at pH 6, 25°C, incubated for 15 days under a 24 hr light-darkness cycle. Bangladesh J. Agril. Res. 32(2) 2007: 255-260.